Assessment of periodontal status in dental fluorosis subjects using community periodontal index of treatment needs - Vandana K; Sesha Reddy M (Wolters Kluwer Medknow Publications, 2007)
Background: Periodontitis is multifactorial in nature. The various determinants of periodontal disease are age, sex, race, socioeconomic status, and risk factors including tobacco usage and oral hygiene status. However, there is inconsistent epidemiological data on the periodontal status of subjects living in high-fluoride areas. The aim of the study was to investigate the effect of dental fluorosis on the periodontal status using community periodontal index of treatment needs (CPITN), as a clinical study. The purpose of this study is to determine the periodontal status using CPITN index in a population aged between 15 and 74 years residing in the high-fluoride areas of Davangere district. The possible reasons for the susceptibility of this population to periodontal disease are discussed. Materials and Methods: 1029 subjects, aged between 15 and 74 years suffering from dental fluorosis were assessed for their periodontal status. Clinical parameters recorded were OHI-S to assess the oral hygiene status, Jackson′s fluorosis index to assess the degree of fluorosis and CPITN index to assess the periodontal status where treatment need was excluded. Results: Gingivitis and periodontitis were more common in females (65.9% and 32.8%, respectively) than in males (75.1% and 24.2%, respectively). Periodontitis was significantly more common in females. As the age advanced from 15 to 55 years and above, gingivitis reduced from 81.0 to 42.9% and periodontitis increased steadily from 18.0 to 57.1%, which was significant. Periodontitis was high in subjects with poor oral hygiene (81.3%), compared to those with good oral hygiene (14.5%), which was significant. As the degree of fluorosis increased, severity of gingivitis reduced and periodontitis increased, i.e., with A degree fluorosis, gingivitis was 89.4% and periodontitis 8.5%, but with F degree fluorosis the former was 64% and the latter 35.8%, which was statistically significant. Conclusion: The results suggest that there is a strong association of occurrence of periodontal disease in high-fluoride areas. The role of plaque is well understood in contrast to the effect of fluorides on periodontal tissues. It goes a long way to reason out fluoride as an important etiological agent in periodontal disease.